Análise do potencial tecnológico do camarão "saburica" (Macrobrachium jelskii, Miers, 1877) no desenvolvimento de produtos e determinação do teor de carotenoides totais - Cirilo, Ana Tereza de Oliveira (2011)
The species Macrobrachium jelskii (MIERS, 1877) (Crustacea, Decapoda, Palaemonidae) known popularly in Brazil as shrimp “sossego” and in the state of Sergipe and shrimp “saburica” is found in the Lower San Francisco river of the state Sergipe/Brazil., where the environment has characteristics that favor its development. The development of derivative products “flavorings powder”, measurement of their nutritional content and analysis of carotenoids, spectrophotometry UV-VIS, chromatography and high performance liquid chromatography HPLC-DAD, can provide information to make better use of technology species, which was the aim of this work. The average length and weight of fresh shrimps and salted/cooked was 0.23g and 32.7mm and 0.16g and 26.02mm, respectively. The average yield for the product of shrimp flavoring “saburica” for samples from the fresh specimens was lower (20.4%) than for the salted cooked (48.36%). The fresh shrimp showed physical characteristics (granulometry), chemical (protein and chlorides) and nutritional value were significantly different. The highest yield of carotenoids (53.423 g / g) was obtained from the extract solution with solvent acetone: hexane (1:1) in the sample of flavoring powder "from the fresh shrimp Saburi. The extraction of the pigments in vegetable oils showed lower yields compared to organic solvents, and soybean oil was more effective than the sunflower. In sensory evaluation, the crackers, s panelists detected no significant differences in the attributes of appearance, aroma, texture and overall impression, according to various concentrations of flavoring used in cookies. However, these differences were observed in flavor attribute in which the tasters preferred the lowest concentration of the formulation of flavoring (3%).